Potentials and prospects of marine aquaculture A window view from Lakshadweep Island - M U, Rekha; Kumar, T T Ajith; Sarkar, U K (Indian Farming, 2024)
Lakshadweep comprises the only coral atolls in the country and 36 islands are scattered in the Arabian Sea. The major source of income for the local community is fishing and coconut-based activities, and there is no potential scope for additional/alternate income from other sources. It is very much needed to explore and provide a source of income generation to the local community at Lakshadweep with fisheries-related activities, which they can able to adopt easily. In this context, the ICAR-National Bureau of Fish Genetic Resources (NBFGR) took an initiative at Agatti Island of Lakshadweep on ornamental organisms breeding and rearing. The simplified technology is being disseminated through community aquaculture for native women inhabitants as an additional/ alternate livelihood option. This is a unique venture, where societal development and conservation are taken up hand-in-hand through the use of indigenous organisms. The present study demonstrates the successful adaptation and utilization of the technology of marine shrimp-based ornamental farming through capacity-building initiatives that involve community participation and a well-structured adaptation process.